THE EFFECT OF GOVERNMENT EXPENDITURE ON INCOME INEQUALITY AND POVERTY IN INDONESIA - Alamanda, Alamanda (Polytechnic of State Finance STAN, 2020)
Income inequality and poverty have become key issues in development studies since the 1970s. Although theoretically there are various factors associated with the incidence of poverty and income inequality, choices regarding the types and structure of government expenditure are often quoted as one of the crucial determinants. However, the evidence is still inconclusive, and the research about these issues in the case of Indonesia is still minimum. This paper tries to contribute to the discussion by analysing a panel data set of 33 provinces from 2005 to 2017 to examine the effect of different types of government expenditure on income inequality and poverty in Indonesia. Using the fixed effect, random effect, and Seemingly Unrelated Regression (SURE) system, this paper finds that social aid, subsidy and grant expenditure have an insignificant effect on reducing income inequality and poverty in Indonesia. However, the empirical evidence suggests that infrastructure spending has a negative correlation with income inequality in urban areas (when using the random effect model), and rural areas (when using the fixed effect model). In addition, infrastructure expenditure is also negatively and significantly correlated with poverty in Indonesia, and the impact is more significant in rural than urban areas.